INFLUENCE OF EUROPEAN VALUES ON PATRIOT-STATESMAN’S DEVELOPMENT - Holovchuk, S. (Педагогічна освіта: Теорія і практика. Психологія. Педагогіка., 2017)
This article analyses the influence of European values on patriot-statesman’s development. Knowledge of European values gives opportunity to make complex characteristics on the following issue taking into account socio-cultural, economic, demographic, geographic, religious and other peculiarities; helps to identify the level and character of influence of religious and ethical teachings on establishment and functioning of European values; creates a respectful and careful attitude to the historical heritage and cultural traditions of the peoples of Ukraine and abroad, tolerant perception of social, religious and cultural differences. Patriotic education is impossible without international one, love and respect for other people, especially our neighbours. The value of international education, in our opinion, means that people of different nationalities understand and enrich each other spiritually, study national identity, culture and customs of the peoples who live nearby, because the use of a different historical and cultural heritage is one of the means of international education, which gives the opportunity to understand better both the meaning of patriotic education of youth, to form a national identity, however, the content of national consciousness keeps people’s historical memory about their past, present, certain ideas, dreams and hopes for the future. Liberal fundamental human rights and freedoms, democratic principles of state management as well as legal and social state are the core of European values. As a combination of liberal and democratic ideas, European values are designated as “liberal and democratic” ones. They have become the principles of functioning of state and political institutions of modern European countries and the European Union. Modern Ukrainian education is aimed at civil identity development, regardless of national-ethnic, gender, cultural and linguistic ones.